Politische Erinnerungen des Vorsitzenden des Alldeutschen Verbandes 1915-1933/36 - Claß, Heinrich (Deutsche Geschichtsquellen des 19. und 20. Jahrhunderts (DGQ), 2023)
»Heinrich Claß. Political Memoirs of the Chairman of the Pan-German League (1915-1933/36)«: The edition of the memoirs of Heinrich Claß, chairman of the Pan-German League, discloses the networks of the so-called »national opposition« in Germany, which propagated ordering concepts of a völkisch civil-military dictatorship. After WWI, Austria also caught Claß´ attention as an additional playground for mobilization and political activism. Cooperation with the NSDAP furthered unmissable competition over leadership of Weimar´s Right. The failure of the DNVP to enclose the National Socialists in their bid for power only concluded the transition of the Pan-German League as the most influential pressure group of the radical bourgeois Right from Imperial Germany to an interest group of outdated notables in the Weimar Republic.